Computerized value stream system (CVSS) to reduce waste in lean manufacturing operation - Hasan, S.; Ahmad, A. N. A.; Feriyanto, D. (2015)
Lean manufacturing is a popular method of acquiring efficiency in manufacturing environment. Value stream mapping (VSM) is one of the methods that can be used by practitioner to support lean. VSM method is also a common method to identify waste and determined causes of the waste through the value stream mapping approach and propose solutions to improve workplace environment. This project is an attempt to computerize the normally manual VSM process. Computerize value stream system (CVSS) is basically a method which is an internet networking system combined with traditional concept of value stream mapping method used at manufacturing company to reduce wastes. This paper summarizes the way to apply an internet, online and network based of an efficient computerize value stream system to improve operation value of the manufacturing company. This paper reviews the design of the package that will replace the manual method of doing VSM. The system is tested in a real shop floor environment and found to be successful.